Peran Musik : Proses Pembuatan Rumah adat Suku Karo “Siwaluh Jabu” di Desa Budaya Lingga - Arya Adha Prananda; Bondan Aji Manggala (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to examine the role of music in the construction process of the traditional Karo house, Siwaluh Jabu, in Lingga Cultural Village, Karo Regency, North Sumatra. In Karo culture, music is not merely a source of entertainment but serves as a symbolic and spiritual medium that reflects cultural values, social cohesion, and the community’s belief system. This study employs a qualitative descriptive method with an ethnographic approach through field observation, in-depth interviews with traditional figures, musicians, and local residents, as well as documentation of rituals and architectural elements of the Siwaluh Jabu house. The findings reveal that music plays a significant role in each stage of construction, starting from the selection of suitable wood to the completion ritual known as Mengket. The Gendang Lima Sendalanen ensemble—particularly through the performance of Gendang Limapuluh Kurang Dua—functions as a medium connecting humans with ancestral spirits, legitimizing the spiritual presence within the house, and strengthening communal cooperation. Music serves not only to regulate the rhythm of collective work but also to ensure harmony between humans, nature, and the unseen forces that are believed to inhabit the house. Therefore, music is an essential element that maintains cultural continuity, reinforces identity, and supports the preservation of the Karo intangible heritage amidst ongoing modernization.